The association between home smoking restrictions and youth smoking behaviour: a review. Issue 6 (18th September 2010) - Emory, Kristen; Saquib, Nazmus; Gilpin, Elizabeth A; Pierce, John P
Abstract : Objective: To review the available evidence for home smoking restrictions as a useful tool in the prevention of youth smoking and to make recommendations for further research. Methods: A PubMed search (1 January 1990 to 26 January 2010) identified studies involving youth ≤18 years using extensive criteria. In all, 17 studies relating home smoking restrictions to youth smoking behaviour were identified from titles, abstracts or the full text, as required. Two additional articles were identified by other means. KE, NS and EG reviewed the studies. Differences in interpretation were resolved by discussion, with EG making final decisions. Results: Of the 19 studies, 16 (including the only 2 longitudinal studies) showed at least marginal evidence of an association of home smoking restrictions with reduced adolescent smoking behaviours. Associations were more numerous and stronger in homes without adult smokers, suggesting that even in such homes, lack of a smoke-free home may undermine the parental value of not smoking. Definitions of home smoking rules, adolescent smoking behaviour and treatment of parental smoking varied widely among studies. It is recommend that future research: (1) contrast smoke-free homes for everyone against all others, (2) included an interaction term for parental smoking and having a smoke-free home, or conduct separate analyses for homes with and without parental or other adults smokers and (3) examine early and later stages of the smoking uptake continuum. Conclusions: While the evidence is suggestive for an effect, further research is required to establish causality using longitudinal designs.